Fenton Oxidation of Methyl Violet in Aqueous Solution - Saeedeh Hashemian; Masoumah Tabatabaee; Margan Gafari (Journal of Chemistry)
In this study, oxidative discoloration of methyl violet (MV) dye in aqueous solution has been studied using Fenton (Fe2+/H2O2) process. The parameters such as concentration of Fe2+, H2O2, MV, temperature, and Cl− and ions that affected of discoloration in Fenton process were investigated. The rate of degradation is dependent on initial concentration of Fe2+ ion, initial concentration of H2O2, and pH of media. Discoloration of MV was increased by increasing the temperature of reaction. Optimized condition was determined and it was found that the obtained efficiency was about 95.5% after 15 minutes of reaction at pH 3. TOC of dye sample, before and after the oxidation process, was determined. TOC removal indicates partial and significant mineralization of MV dye. The results of experiments showed that degradation of MV dye in Fenton oxidation can be described with a pseudo-irst-order kinetic model. The thermodynamic constants of the Fenton oxidation process were evaluated. The results implied that the oxidation process was feasible, spontaneous, and endothermic.